A Multidisciplinary Approach to Public HealthCrises: Insights from Epidemiology, Nursing, Family Medicine, Psychology, and Health Informatics - Omar Saleh Alzaid,; Ali Mohsen Khallaf Alhazmy,; Khalaf Salem Enad Alsabilah,; Abdullah Abdulaziz Ibrahim Alkodiri,; Hassan Ahmad Mogbel Sharahili,; Fawzya Mohammad Abu Hadi,; Mohammad Saleem Alenezi,; Wejdan Sulaiman Alharbi,; Fawziah Saud A Al Zaynaldeen,; Saud Nahed Saud Aldawsari,; Amer Hussein Ali Al Khurim, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Multidisciplinary approaches produce more effective public health solutions. Integrating knowledge from several disciplines, including epidemiology, psychology, and health policy, enhances understanding of health concerns and fosters public health initiatives. Improved responses to health crises, like the COVID-19 pandemic, demonstrate the effectiveness of a multidisciplinary strategy in understanding and reducing disease spread. Interdisciplinary collaboration has enhanced innovation in public health research methods and practices. Studies demonstrate that interdisciplinary collaboration can produce new and adaptable strategies for addressing intricate health challenges. Monodisciplinary methods can uncover innovative, effective, and pragmatic solutions that are frequently inaccessible. Although multidisciplinary techniques provide considerable benefits, they also present problems with team collaboration and inter-disciplinary communication. Enhancing governmental support for interdisciplinary collaboration, encompassing flexible funding and policies that integrate science.